(untitled) (Sociologisk Forskning, 2016)
Normalizing problematized youth by governing their parents: From structural explanations to family-centred solutions The current article explores the ways that organizational representatives outline the causes of and propose solutions to the problematic behaviour of youth living in, what is described as, an immigrant neighbourhood in a Swedish city. The empirical material, consisting of interviews with representatives from various organizations (such as the police, schools, social services and NGOs) as well as field observations, has been analyzed using the theory of governmentality. The causes of problematic youth behaviour are related to disadvantaged immigrant urban space, unemployment, unstable home situations and family relations, and parents’ deviant norms, knowledge and culture. In the discourses about causes and solutions, a recurring frame of reference is the issue of immigration in general and parent’s migrant background in particular. In spite of the complexity of the proposed causes, the pronounced solutions are directed towards the fostering of immigrant parents, the establishment of zones of communication and early prevention. Hence, the prevailing solutions are permeated by discourses of activation of parents.